EFFECTIVENESS OF AN AIR PURIFICATION SYSTEM IN REDUCING AIRBORNE MICROBIAL LOAD IN THE NEUROSURGICAL INTENSIVE CARE UNIT AT CHO RAY HOSPITAL: AN INTERVENTION STUDY (Vietnam Journal of Community Medicine, 2026)
Background: Hospital acquired infection control in intensive care units remains a major challenge because the air environment is highly susceptible to contamination by microbial aerosols posing a significant risk of cross infection for critically ill and immunocompromised patients.Objective: To evaluate the effectiveness of air purifiers in reducing microbial density in the air at the Neurosurgical Intensive Care Unit, Cho Ray Hospital.Methods: A cross-sectional intervention study was conducted with 162 air samples collected before and after installation of air purifiers from February 2022 to September 2022. Microbial density was quantified by culture-based methods and expressed in CFU/m³.Results:. The total aerobic bacterial count decreased significantly after the intervention, with the most notable reduction observed at week 1 and month 2. The densities of Coagulase-negative Staphylococcus and Bacillus spp. also declined and remained stable throughout the follow-up period. Mold spores decreased progressively after the second week when room temperature was stabilized. Importantly, pathogenic bacteria such as Pseudomonas aeruginosa and Klebsiella spp. markedly decreased after one week and were no longer detected at subsequent time points.Conclusion: Air purifiers effectively improved air quality in the intensive care setting, particularly in reducing clinically significant airborne pathogens.
Keywords: Air purifier, infection control, intensive care unit.